Dystrophin and dystrophin-associated protein in muscles and nerves from monkey - M Royuela; D Chazalette; F Rivier; G Hugon; R Paniagua; V Guerlavais; JA Fehrentz; J Martinez; D Mornet (European Journal of Histochemistry, 2009)
Since all organs (i.e. skeletal, cardiac, smooth muscles and sciatic nerve) are never only taken from a single patient, all these tissues were obtained from one cynomolgus monkey, a model closely resembling humans. This work describes an up-to-date reinvestigation of the dystrophin-glycoprotein complex and related molecules in various monkey tissues such those cited above.We used monoclonal and polyclonal antibodies produced in our laboratory, which are directed against dystrophin, utrophin, short-dystrophin products, a- dystrobrevin, b-dystroglycan, a-syntrophin, a-, b-, g-, d-, e- sarcoglycan, and sarcospan. For each molecule, we determined their molecular weight and tissue localization. Regardless of the tissue analyzed, at least one dystrophin or utrophin as full-length molecule and one short-dystrophin product or dystrobrevin as proteins belonging to the dystrophin superfamily were found. b-dystroglycan, b and d sarcoglycans were always detected, while other sarcoglycans varied from all to only three components. e sarcoglycan appears to be specific to smooth muscle, which is devoid of a sarcoglycan. Sarcospan is only absent from sciatic nerve structures. Among the different muscles investigated in this study, short dystrophin products are only present in cardiac muscle. All of these findings are summarized in one table, which highlight in one single animal the variability of the dystrophin-glycoprotein complex components in relation with the organ studied. This statement is important because any attempt to estimate protein restoration needs in each study the knowledge of the expected components that should be considered normal.